Screening of Y-STR INRA189 polymorphism in Indian breeds of Buffaloes - Deswal, Siddharth (Indian Journal of Dairy Science, 2019)
In present study we explore Y specific STR INRA189 polymorphism in Indian breeds of buffaloes. A total of 139 semen samples of five different Indian buffalo breeds were collected for the study. DNA was extracted using standard phenol chloroform method.Previously reported fluorescent labelled primer were standardised at annealing temperature of 58ºC for PCR amplification. Further, the genotyping was done using capillary electrophoresis on ABI 3730 instruments (Applied Biosystems) and data was analysed in GeneMapper software. With previously reported allele size range in cattle and African buffalo, the microsatellite marker INRA189 was found to have only one allele of 173 bp size in all five breeds of buffalo (Murrah, Mehsana, Nili-Ravi, Surti and Jaffarabadi). INRA189 Y specific STR was found to be monomorphic in Indian breeds of buffalo.